The Home Literacy Environment as a Predictor of the Early Literacy Development of Children at Family-Risk of Dyslexia. (2nd September 2016) - Hamilton, Lorna G.; Hayiou-Thomas, Marianna E.; Hulme, Charles; Snowling, Margaret J.
ABSTRACT: The home literacy environment (HLE) predicts language and reading development in typically developing children; relatively little is known about its association with literacy development in children at family-risk of dyslexia. We assessed the HLE at age 4 years, precursor literacy skills at age 5, and literacy outcomes at age 6, in a sample of children at family-risk of dyslexia ( n = 116) and children with no known risk ( n = 72). Developmental relationships between the HLE and literacy were comparable between the groups; an additional effect of storybook exposure on phoneme awareness was observed in the family-risk group only. The effects of socioeconomic status on literacy were partially mediated by variations in the HLE; in turn, effects of the HLE on literacy were mediated by precursor skills (oral language, phoneme awareness, and emergent decoding) in both groups. Findings are discussed in terms of possible gene–environment correlation mechanisms underpinning atypical literacy development.